Incidents of dental caries in SAD toddlers at risk of stunting in Muaro Jambi - Nurmawi, Yesi; Surayah, Surayah; Primalasari, Septian (Riset Informasi Kesehatan, 2024)
Abstract Background: According to the WHO, the prevalence of dental caries is 81.5% in children aged 3-4 years, 92.6% in those aged 5-9 years, and 90.2% in the 5-year age group. Diet and nutrition can influence oral health, including dental caries, which in turn affects overall health, depending on the types of food consumed. Damage to teeth causes loss of chewing ability in children (masticatory dysfunction), impacting appetite, food intake, and digestion, and causes stunted growth, thus affecting children's eating patterns. This study aims to analyze the relationship between dental caries and stunting in SAD toddlers. Method: This cross-sectional study included 40 children under five years old, selected through stratified random sampling. Data were collected using questionnaires, dental exams, and anthropometry, and analyzed with the Chi-square test. Results: Research found 20.0% incidence of stunting, 32.5% dental caries, and 40% high cariogenic diet. Among SAD toddlers in Muaro Jambi, a significant relationship was found between high cariogenic food consumption patterns and dental caries, as well as stunting. Conclusion: A high cariogenic diet is a contributing factor to dental caries, which is linked to the incidence of stunting in SAD toddlers.